Patriarchal Culture in the Short Story Bayt Min Laḥm by Yusuf Idris. - Annisa Nabila; Yeni Ratna Yuningsih; Minatur Rokhim (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
This study analyzes the representation of patriarchal culture in Yusuf Idris's short story Bayt min Laḥm, which captures the social conditions of post-war Egypt in 1967. This short story shows the limitations of women's roles in the domestic and social realms, as well as how men's existence is positioned as a source of legitimacy of family values and expectations. The narrative centers on three princesses who convince their mother to marry a blind qārī', in the hope that her presence will attract other potential male suitors. However, instead of presenting new hope, the presence of the qārī' creates an atmosphere of fear, suspicion, and psychological pressure that emphasizes women's subordination. This study uses Roland Barthes' semiotic approach with qualitative descriptive methods. The results of the analysis show that women in short stories are depicted as having no social or emotional autonomy without the presence of male figures, thus strengthening the patriarchal dominance structure in the family. The findings of this study confirm that Yusuf Idris's work not only serves as a social critique, but also opens up space for reflection on the position of women in the construction of Egyptian patriarchal culture.